Windows registry forensics advanced digital forensic analysis of the windows registry - Carvey, Harlan (Elsevier Science, 2016)
The second edition provides the most in-depth guide to forensic investigations involving Windows Registry. This book is one of a kind, giving the background of the Registry to help users develop an understanding of the structure of registry hive files, as well as information stored within keys and values that can have a significant impact on forensic investigations. -- Back cover